PENYELUNDUPAN HUKUM INVESTASI ASING LANGSUNG DI INDONESIA - Siti Maryam; Andri Brawijaya (JURNAL ILMIAH LIVING LAW, 2023)
Investing activities to do business in a territory of the Republic of Indonesia carried out by foreigners or what is called Foreign Investment, this research is focused only on the BOPUNJUR region (Bogor-Puncak-Cianjur) which is a tourism area that is widely known both from within and from outside country, its beauty leads tourists to visit and even many investors to invest in the BOPUNJUR area. The purpose of this study is to find out and analyze the problems of foreign investment in the Bopunjur area and also the integrated concept of foreign investment in the Bopunjur area. The method used is normative juridical research with statutory approach and conceptual methods. The research results obtained are that in the Foreign Direct Investment Practices carried out by foreign investors in the BOPUNJUR Region that in its implementation there is a legal smuggling namely the practice of Nominee, dummy, and strawman.